"Pinocchio" with "Zarathustra": which relationship between two such different anthropological models? - Franco Cambi (Firenze University Press, 2015)
This article compares two text written in the late ninetheenth century: Pinocchio and Zarathustra: both texts, even if they are divergent for what concerns narrative style, are Great Myths of our epoch and contain common significant elements.